Vulvar Hemangioma: Case Report - Silva, Janine Medeiros da; Calife, Emily Ramos; Cabral, João Victor de Sousa; Andrade, Hildemárzio Pinheiro Falcão de; Gonçalves, Ana Katherine (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Hemangioma is a benign neoplasm that may affect the vulva, and it can cause functional or emotional disability. This article reports the case of a 52-year-old female patient with a history of a genital ulcer for the past 3 years and who had undergone various treatments with creams and ointments. The patient was biopsied and diagnosed with vulvar hemangioma and was subsequently submitted to surgical excision of the lesion. We emphasize the importance of following the steps of the differential diagnosis and proceeding with a surgical approach only if necessary.
Keywords: ulcer; vulvar neoplasms; hemangioma; biopsy